Synthesis and conductivity behaviour of proton conducting (1-x)Ba0.6Sr0.4Ce0.75Zr0.10Y0.15O3-delta-xGDC (x=0, 0.2, 0.5) composite electrolytes - Jaiswal, Shivendra K.; Hong, Jongsup; Yoon, Kyung J.; Son, Ji-Won; Lee, Jong-Ho (WILEY, 2017)
An attempt has been made here to synthesize (1-x)Ba(0.6)Sr(0.4)CZY-xGDC (x=0, 0.2, 0.5) composite electrolytes and investigated their phase(s), X-ray photo spectra (XPS) and conduction properties. All compositions possess dual phases (perovskite-type as well as cubic fluorite structure) and show proton conduction in various atmospheres. Homogeneous formation and compatibility between phases have been confirmed from X-ray diffraction analysis. Detailed X-ray photoelectron spectroscopy (XPS) studies on the oxidation states of barium, strontium, gadolinium, cerium, zirconium, yttrium, and oxygen was performed. With increasing "x", oxygen vacancy concentration increases as cerium ions in 4+ oxidation state decreases. The conduction behavior of composites depicts the protonic in nature and total activation energy lying in the range of 0.16-0.24 eV. This study indicates that the conductivity increases with GDC content in composite electrolytes and highest conductivity is found for composite with x=0.5. These characteristics are useful to make (1-x)Ba(0.6)Sr(0.4)CZY-xGDC composite electrolytes as promising candidate of central membrane for advanced fuel cell technology.